2020
DOI: 10.1016/j.eats.2019.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Iliac Bone Block Augmentation for Glenoid Reconstruction: Transglenoid Fixation Technique Using an All-Suture Anchor

Abstract: Arthroscopic Bankart repair of anterior instability has shown relatively good results, but its effectiveness is unclear in cases wherein there is a bone defect in the glenoid bone. The surgical management of recurrent anterior shoulder instability with severe glenoid bone loss has been challenging until now. Therefore the Latarjet procedure was introduced as an alternative that provided good results in cases of full instability with a bone defect. In cases of recurrent anterior shoulder instability, bone defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…8,16,50 Secondary to some of these concerns, some novel surgical techniques, which use a nonrigid fixation approach for graft positioning via suture anchors or suture suspensory systems, have been comprehensively described. 2,22,[56][57][58][59] Given a surge of interest, a recent systematic review reported that nonrigid FBB procedures in clinical scenarios resulted in satisfactory functional outcomes and low recurrence rates of instability, revision rates, and complication rates. 29 Some surgeons also determined that nonrigid FBB procedures using bone grafts could achieve bony union radiologically, resulting in the re-creation of glenoid morphological features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,16,50 Secondary to some of these concerns, some novel surgical techniques, which use a nonrigid fixation approach for graft positioning via suture anchors or suture suspensory systems, have been comprehensively described. 2,22,[56][57][58][59] Given a surge of interest, a recent systematic review reported that nonrigid FBB procedures in clinical scenarios resulted in satisfactory functional outcomes and low recurrence rates of instability, revision rates, and complication rates. 29 Some surgeons also determined that nonrigid FBB procedures using bone grafts could achieve bony union radiologically, resulting in the re-creation of glenoid morphological features.…”
Section: Discussionmentioning
confidence: 99%
“…5,30,50 In the N-RF group (Figure 4C), the graft was secured via sutures using a nonrigid suspensory fixation technique, modified from clinical procedures using suture anchors. 22,51,[56][57][58][59] Briefly, 2 superficial, transglenoid 0.5-mm minitunnels (blue arrows in Figure 4C) were created at the anterior rim of the glenoid defect (~2:00 and 4:00) using 0.5-mm K-wire, accompanied by 2 deep, parallel minitunnels drilled on the fresh bone bed at the scapular neck using the same method. Next, two 2-0 Ethibond sutures were passed through 2 paired superficial and deep minitunnels using guide wires, respectively, wrapping the superior and inferior one-third portions of the bone graft, with the inferior sutures passing through the graft holes beforehand (white triangles in Figure 4C).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…As with Boileau's technique, this necessitates the use of a posterior incision to ensure that the button lies flush against the cortex with no soft tissue interposition. Recently, J o u r n a l P r e -p r o o f Jong et al al published a single all suture anchor fixation technique using ICBG 13 . It relied on only one soft giant knot for fixation with the potentially weaker force applied across the graft and reduced graft rotational stability, and the risk of graft toggling.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to Latarjet procedure is offered by arthroscopically performed bone block procedures, including iliac crest autografts or other osteochondral allografts. All-arthroscopic iliac crest autografts augmentation techniques have been reported, including those of Jeong et al [12] using an all-suture anchor, Taverna et al [30] using EndoButton devices, and Scheibel et al [23] using bio-compression screws. These minimally invasive procedures have some potential advantages, including preservation of the subscapularis musculotendinous unit [20], and decreasing the risk of hardware complications because of screw-free graft xation [33].…”
Section: Discussionmentioning
confidence: 99%